Adoption without gains, and vice-versa: Exploring the disconnect between improved bean varieties and yield in Central America and Haiti through the lens of seed systems - Reyes, Byron; Maredia, Mywish K.; Martínez, José María; Gomez, Lorena; Rosas, Juan Carlos; Miranda, Angela (Elsevier, 2025)
Context: Common beans (Phaseolus vulgaris L.) are vital for food security and rural livelihoods in Central America and Haiti. Over the past 30 years, R&D has focused on breeding resilient bean varieties to withstand climate change, pests, and diseases. However, the success of these innovations depends not only on variety development but also on efficient seed systems that deliver them to farmers—a crucial yet often overlooked factor in maxi-mizing agricultural R&D benefits. Objectives: This study evaluates the adoption of improved bean varieties and associated yield differences across Guatemala, Honduras, Nicaragua, and Haiti. It also assesses the extent to which current seed systems facilitate or constrain adoption and potential yield outcomes. Methods: This study used a mixed-methods approach, combining DNA fingerprinting, farmer surveys, on-farm field trials, and expert interviews to assess adoption of improved varieties. Regression analysis was used to examine yield differences, controlling for observable factors. Results: Adoption estimates ranged from 10 % (Nicaragua) to 77 % (Haiti). Only Nicaragua—despite low adoption—showed a significant yield gain (~33 % at p < 0.05). In contrast, Guatemala, Honduras, and Haiti recorded no gains despite moderate to high adoption reported by experts (Honduras and Guatemala) or confirmed by DNA analysis (Haiti). DNA evidence reveals contamination in formal seed channels, while survey data and expert opinion suggest that limited support services may constrain performance. Significance: Adoption alone is not a sufficient metric of success. Ensuring genetic integrity, local adaptation of varieties, and effective delivery systems is critical for translating research investment into yield benefits. Strengthening seed quality control, aligning bean breeding with farmer needs, and supporting informal systems are key to maximizing impact.